Synthetic dimensions for topological and quantum phases - Javier Argüello-Luengo; Utso Bhattacharya; Alessio Celi; Ravindra W. Chhajlany; Tobias Grass; Marcin Płodzień; Debraj Rakshit; Tymoteusz Salamon; Paolo Stornati; Leticia Tarruell; Maciej Lewenstein (Communications Physics, 2024)
Abstract The concept of synthetic dimensions works particularly well in atomic physics, quantum optics, and photonics, where the internal degrees of freedom (Zeeman sublevels of the ground state, metastable excited states, or motional states for atoms, and angular momentum states or transverse modes for photons) provide the synthetic space. In this Perspective article we report on recent progress on studies of synthetic dimensions, mostly, but not only, based on the research realized around the Barcelona groups (ICFO, UAB), Donostia (DIPC), Poznan (UAM), Kraków (UJ), and Allahabad (HRI). We describe our attempts to design quantum simulators with synthetic dimensions, to mimic curved spaces, artificial gauge fields, lattice gauge theories, twistronics, quantum random walks, and more.